Devising an energy saving technology for a biogas plant as a part of the cogeneration system - Чайковська, Євгенія Євстафіївна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper suggests an operation technology for a biogas plant that allows setting a heating medium temperature at the inlet to the heat exchanger built in a digester and measuring the heating medium temperature at the outlet. An integrated system for assessing the varied temperature of digestion (that is based on mathematical and logical modeling within the cogeneration system) secures a continuous gas outlet, a timely unloading of fermented mash and loading of a fresh matter. For this purpose we have devised the following structural schemes: (1) a complex mathematical modeling of the dynamics of a biogas plant and a heat exchanger built in a digester, (2) a logical modeling of a biogas plant efficiency control, which allows obtaining functional data at the level of making decisions, (3) a logical modeling of making decisions within the cogeneration system, (4) a logical modeling of a biogas plant state, which allows confirming the made decisions. The devised operation technology for a biogas plant as a part of the cogeneration system enables saving 25.4 thsd m3of biogas per year, if we use, for instance, a heat pump and manufacture 352.5 m3of biogas per day. Raising a biogas plant marketability by 13.94 % would reduce the cost of electricity and heat within the range of 20.0-30.0 %.